Work-Family Balance: Challenges, Experiences and Implications for Families in Qatar - Doha International Family Institute (Hamad Bin Khalifa University Press, 2019)
This study aims to understand the reality of work-family balance in Qatar, providing evidence to inform policy formation and development and introduce related implementation standards. The ultimate goal is to ensure the protection and empowerment of Qatari families through these policies. This study applied mixed methods approach, where a qualitative part was based on in-depth interviews with working Qatari adults from both genders, and a quantitative study conducted through a survey. This was designed to understand the factors that constitute or prevent attaining such balance and describe the challenges, and the consequences of the lack of balance. The study concludes a set of recommendations that revolve around reviewing related work-family balance policies, such as limiting the work hours and introducing flexible working hours, expanding paid maternity leave and subsidizing high-quality childcare for all children below compulsory education age, and allowing both parents a paid time to accompany a sick child during treatment.